Distinct classical and molecular cytogenetics of Astyanax marionae and A. fasciatus (Characiformes: Characidae): a comparative study of the organization of heterochromatin and repetitive genes - Piscor, Diovani [UNESP]; Centofante, Liano; Parise-Maltempi, Patricia Pasquali [UNESP] (Springer Nature, 2017)
Genus Astyanax is well distributed in Neotropical freshwater environments and its taxonomic position is uncertain, as is the case with other Characidae genera allocated in the group incertae sedis. This study aimed to analyse the karyotype of different populations of Astyanax fasciatus (Corumbataí River basin) using Giemsa staining, C-band technique, and fluorescence in situ hybridization for the H3 histone and 5S rRNA genes, in addition we describe for the first time the chromosomal organization of H3 histone and 5S rRNA genes in A. marionae (Paraguay River basin). Chromosomes of three A. fasciatus populations were analysed (two with 2 n= 50 and one with 2 n= 48) and the heterochromatin was organized in two forms (blocks with blurred boundaries and distinct blocks). H3 histone and 5S rRNA genes were observed in all the three populations of A. fasciatus on two chromosome pairs (one metacentric chromosome showing H3 histone and 5S rRNA gene clusters). In A. marionae (2 n= 48), H3 histone and 5S rRNA genes were observed in one acrocentric chromosome pair (different pairs). Further, differences between karyotypes and heterochromatin, as well as the chromosomal organization of H3 histone and 5S rRNA genes in Astyanax species, focussing on chromosome evolution in the group are discussed.
Keywords: 5S rDNA; Astyanax fasciatus; C-band; chromosomes; H3 histone gene